PRODUCT QUALITY, PROMOTION AND SERVICE TO CUSTOMER SATISFACTION TELKOMSEL INTERNET DATA CARD AT WONOGIRI - Sely Dwi Saputri; Bambang Mursito; Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine the quality of products, promotions and services on customer satisfaction of Telkomsel internet data card package in Wonogiri. This type of research is quantitative. This research was conducted in Wonogiri, the number of population is not infinite because of the large number of internet data package users, especially Telkomsel which has a very stable network. The samples taken in this study were 100 respondents. Sampling using purposive sampling technique. The method of data analysis uses multiple oline are regression analysis. The results of this study indicate that the results of the F test show that product quality promotion and service simultaneously have a significant effect on customer satisfaction of Telkomsel's internet data packet card in Wonogiri. The results of the t test show that the product quality partially has a positive and significant effect on customer satisfaction of Telkomsel internet data package cards in Wonogiri. Promotion variables partially also have a positive and significant effect on customer satisfaction of Telkomsel internet data package card customers in Wonogiri. Service variables partially also have a positive and significant effect on customer satisfaction of Telkomsel's internet data package card in Wonogiri. Product Quality, Promotion and Good Service in order to increase Customer Satisfaction of Telkomsel Internet Data Package Card in Wonogiri. Keywords: Product Quality, Promotion, Service and Customer Satisfaction.